Gasoline and diesel passenger car emissions deterioration using on-road emission measurements and measured mileage. (April 2022) - Davison, Jack; Rose, Rebecca A.; Farren, Naomi J.; Wagner, Rebecca L.; Wilde, Shona E.; Wareham, Jasmine V.; Carslaw, David C.
Abstract: Modern gasoline and diesel vehicles are equipped with highly effective emission control systems that result in low emissions of pollutants such as nitrogen oxides (NOx ) when new. However, with increasing age or mileage, the emissions performance of vehicles can deteriorate over time, leading to increased emissions. In this work we use comprehensive vehicle emission remote sensing measurements collected over a wide range of conditions, together with individual vehicle measured mileage to quantify vehicle emissions deterioration. A quantile regression modelling approach is used to provide a more complete understanding of the distribution of deterioration effects that is not captured by considering mean changes over time. The approach accounts for factors such as driving conditions and ambient temperature, as well as determining whether deterioration affects whole populations of vehicles or a smaller subset of them. Accounting for these factors, we find that for most pollutants the rate of deterioration of emissions from pre-Euro 5 gasoline passenger cars is highly skewed. Between 5% and 10% of pre-Euro 5 gasoline passenger cars have emissions similar to a Euro 5 diesel car, suggesting that policies should be developed to accelerate their removal from the fleet. Furthermore, we find evidence that there are differences between vehicle manufacturers in the way emissions of NOx deteriorate. Graphical abstract: Image 1 Highlights: 197, 000 vehicle emission remote sensing measurements coupled with individual measured mileage data from vehicle inspections. Quantile regression framework used to examine distribution of deterioration effects of passenger car NOx and PM emissions. Rate of deterioration for gasoline NOx emission controlled by small proportion of vehicles. Large fleet coverage of remote sensing is exploited to examine manufacturer-specific NOx emission deterioration.